2011
DOI: 10.1007/s00221-011-2846-1
|View full text |Cite
|
Sign up to set email alerts
|

To know or not to know: influence of explicit advance knowledge of occlusion on interceptive actions

Abstract: This study examined how explicit advance knowledge might influence adaptive behavior to visual occlusions. Catching performance and kinematics of good ball catchers were compared between no, early and late occlusion trials. Discrete visual occlusions of 400 ms, occurring early or late in the ball's approach trajectory, were randomly interspersed between no occlusion trials. In one condition, the presence and type of occlusion were announced a priori (expected), whereas in another condition no such information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
(61 reference statements)
1
11
0
Order By: Relevance
“…A number of studies have reported that visual occlusion can influence the movement pattern in manual catching (Dessing, Oostwoud-Wijdenes, Peper, & Beek, 2009; Mazyn, Savelsbergh, Montagne, & Lenoir, 2007; Tijtgat, Bennett, Savelsbergh, De Clercq, & Lenoir, 2011). Mazyn et al (2007) asked participants to catch an approaching ball with full vision and in a visual occlusion condition in which the ball was occluded at the onset of catching hand-movement.…”
Section: Model-based Control: Is An Internal Model Sufficient?mentioning
confidence: 99%
“…A number of studies have reported that visual occlusion can influence the movement pattern in manual catching (Dessing, Oostwoud-Wijdenes, Peper, & Beek, 2009; Mazyn, Savelsbergh, Montagne, & Lenoir, 2007; Tijtgat, Bennett, Savelsbergh, De Clercq, & Lenoir, 2011). Mazyn et al (2007) asked participants to catch an approaching ball with full vision and in a visual occlusion condition in which the ball was occluded at the onset of catching hand-movement.…”
Section: Model-based Control: Is An Internal Model Sufficient?mentioning
confidence: 99%
“…Along these lines, psychophysical experiments have suggested short-term adaptations in the motion extrapolation process by observing that early and late occlusion of the visual target may affect differentially the spatial features of catching movements, depending on the presentation order of the occlusion conditions [77]. In addition to short-term mechanisms, abstract long-term categorical representations of the target motion [78], as well as explicit advance information [79] can contribute to this process. Moreover, the evidence that occluding vision for short intervals before interception of vertically free-falling targets with natural and non-natural laws of motion can produce errors consistent with temporal estimates based on an implicit knowledge of the causal effects of Earth's gravity implies a role also for internal models of the external environment [80].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to examine the effects of visual occlusion created by the wall on goalkeeper performance during free kicks. Because the wall causes the ball to come into view later we predicted a delayed movement onset [12][13]. Since this leaves less time to complete the interception and because the wall occludes the initial ball motion, we expected the wall to reduce performance and particularly so for shorter flight times [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…For the time-pressed task of blocking penalty kicks goalkeeper performance strongly depends on seeing the kicker [4][5][6][7][8]; free kicks allow more time for online control and goalkeeper performance in this context does not critically depend on seeing the kicker [9][10][11]. Early occlusion of the ball trajectory will likely result in later initiation and reduce catching performance [12][13], due to less information and less time being available to guide the interception.…”
Section: Introductionmentioning
confidence: 99%